2021
DOI: 10.3390/jmse9111310
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Spatial and Temporal Distribution and Environmental Characteristics of Polychaete Assemblages in the Coastal Waters of Ulleungdo, East Sea of Korea

Abstract: The coastal area of Ulleungdo in the East Sea has experienced large climate and environmental changes. However, research on marine benthic animals in this area has been very limited. In the present study, we investigated the spatial and temporal distribution of benthic polychaetes to determine their seasonal adaptability to environmental changes in the coastal waters of Ulleungdo in 2019. In total, 116 species (34 families) of polychaetes were identified with an average of 25 species per site. The average dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…In contrast to Kola Bay, other studies have shown the highest contributions to the total benthic biomass for echinoderms (mainly sea urchins) and bivalves or barnacles [21,66,69]. The observed differences in the structure of benthic communities along a gradient of environmental factors in Kola Bay (Table 2, Figure 2) agree with those found in several estuarine systems with expressed salinity gradients [70][71][72][73].…”
Section: Benthic Communitiessupporting
confidence: 77%
“…In contrast to Kola Bay, other studies have shown the highest contributions to the total benthic biomass for echinoderms (mainly sea urchins) and bivalves or barnacles [21,66,69]. The observed differences in the structure of benthic communities along a gradient of environmental factors in Kola Bay (Table 2, Figure 2) agree with those found in several estuarine systems with expressed salinity gradients [70][71][72][73].…”
Section: Benthic Communitiessupporting
confidence: 77%
“…The South Korean government had long discussed the necessity of such an establishment. The surrounding waters include various invertebrates [20,21]. Figure 2 shows the waters surrounding the northern and western parts of Ulleungdo as a marine protected area.…”
Section: Necessity Of Establishing Marine Protected Areas In Dokdomentioning
confidence: 99%
“…In addition, these islands are known to have unique environmental and biological characteristics that are considerably different from those of mainland coastal regions at the same latitude (Kang et al, 2013;Kang et al, 2019;Chung et al, 2020;Kim et al, 2020). In particular, the coastal ecosystems of Ulleungdo and Dokdo are characterized by high biodiversity and are home to several endangered and endemic species (usually, marine invertebrates and plants) (Song et al, 2017;Kim and Yu, 2021;Kim et al, 2023). Thus, to understand the ecological features of these islands as biological hotspots, it is necessary to characterize the structure and function of marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%